A privileged ternary blend enabling non-fullerene organic photovoltaics with over 14% efficiency. Issue 43 (20th July 2020) - Yan, Jing; Yi, Yuan-Qiu-Qiang; Zhang, Jianqi; Feng, Huanran; Ma, Yanfeng; Wan, Xiangjian; Li, Chenxi; Wei, Zhixiang; Chen, Yongsheng
Abstract : Two non-fullerene small molecule acceptors, NT-4F and NT-4Cl, were designed and synthesized. Power conversion efficiencies of 11.44% and 14.55% were achieved for NT-4Cl -based binary and ternary devices, respectively. Abstract : Two non-fullerene small molecule acceptors (NF-SMAs) NT-4F and NT-4Cl with halogenated end groups were designed and synthesized. When blended with PM6, the NT-4Cl -based binary device gave a power conversion efficiency (PCE) of 11.44% with a fill factor (FF) of 74.1% while the NT-4F binary system showed a PCE of 9.46%. To further broaden the absorption profile and fine-tune the morphology, NCBDT-4Cl, an acceptor with a similar chemical structure and identical molecular orientation to NT-4Cl, was selected as a combinatory component to the PM6 :NT-4Cl system. As a result, the ternary device achieved a dramatically promoted PCE of 14.55% with a synergistically enhanced FF of 77.1% and a J sc of 20.99 mA cm −2 as well as a decreased energy loss ( E loss ) of 0.51 eV, which represents the best performance for NT-based NF-SMAs to date.